COMPETITION CULTURE AS AN OBJECT OF PHILOSOPHICAL ANALYSIS (E Global Congress, 2024)
Competition is a very broad concept that covers many aspects within its framework, such as positive and negative, effective and ineffective, consequential or useless, that only prioritize one's own interests or move for the benefit of the community.